Smartphones e profissionais: amigos e inimigos - Bruzzi, Pedro Pinto (2013)
The use of Information Technologies Mobile and Wireless (TIMS) artifacts brings up a number of associated technological paradoxes, already identified in the literature. The increase in use of TIMS and its evolutions eventually enabled new types of uses and interactions. Based on theories about the existence of paradoxes associated with the use of technological equipment, especially TIMS, this study sought to verify the relationship between smartphones and professionals. Starting with a data collection through a structured survey, this research used quantitative analysis and aimed to determine the presence and measure the intensity of the technological paradoxes identified in the literature, upon statistical professional use of smartphones. Another issue observed in this study was the association between these technological paradoxes and also the identification of factors that could impact the perception of these paradoxes associated with smartphone use by professionals who use them. Data analysis has shown which of the fourteen technological paradoxes presented by Mick and Fournier (1998), Jarvenpaa and Lang (2005) and Mazmanian et al. (2006) were perceived by most respondents, highlighting the paradox of autonomy and addiction, which was experienced by more than 85% of those who responded to the survey. Based on the percentage of respondents who perceive the paradoxes and considering its strengths, this paper also presents a ranking of their forces, determined by the rate of relative paradox strength. This ranking provides in the top positions the following ambiguities: autonomy / addiction, engagement / disengagement and freedom / slavery, respectively. Another contribution of this study was that none of the analyzed paradoxes are statistically independent. Finally, conducting an ordinal logistic regression with the data collected led to the conclusion that only two of the paradoxes considered are impacted by the independent variables observed.